Development of Interactive Physics Learning Website Based On STEAM Approach to Increase Student Learning Motivation in Optics Chapter - Agusti Mahendra; Binar Kurnia Prahani; Muhammed Akif Kurtuluş (Universitas Negeri Surabaya, 2025)
Objective: Changing times and technological advances influence the world of education. Therefore, prospective educators are required to be able to utilize existing technology in classroom learning activities. This research aims to produce Physics learning media by applying the STEAM approach to increase student learning motivation on optics. The learning media developed is an interactive Physics learning website based on the STEAM approach. Method: The type of research conducted is the development of learning media. The media development model used is the ADDIE model. The learning media trial was conducted at SMAN 1 Gedangan with a research sample of 10 students. The instrument used in this study was a student response questionnaire. The data analysis technique used was quantitative descriptive analysis. Results: The results showed that the effectiveness of learning media in increasing student learning motivation had a score of 90.4% with very positive criteria. The developed learning media is effectively used in learning physics on optics. Based on the results of data analysis, it can be concluded that the interactive physics learning website based on the STEAM approach is feasible (very effective) in increasing student learning motivation.Novelty: Integrating the STEAM approach in this learning media provides a learning experience that combines theory with creativity, art, and problem-solving. Unlike conventional methods, the website features interactive tools to explore physics concepts through simulation and visualization, thus increasing student motivation and engagement.